Emerging Roles of Non-proteolytic Ubiquitination in Tumorigenesis - Yin, Xiu; Liu, Qingbin; Liu, Fen; Tian, Xinchen; Yan, Tinghao; Han, Jie; Jiang, Shulong (Frontiers in Cell and Developmental Biology, 2022)
Ubiquitination is a critical type of protein post-translational modification playing an essential role in almost all cellular processes. To date, more than eight types of ubiquitination exist, all of which are involved in distinct cellular processes based on their structural differences. Studies have indicated that activation of the ubiquitination pathway is tightly connected with inflammation-related diseases as well as cancer, especially in the non-proteolytic canonical pathway, highlighting the vital roles of ubiquitination in metabolic programming. Studies relating degradable ubiquitination through lys48 or lys11-linked pathways to cellular signaling have been well-characterized. However, emerging evidence shows that non-degradable ubiquitination(linked to lys6, lys27, lys29, lys33, lys63, and Met1) remains to be defined. In this review, we summarize the non-proteolytic ubiquitination involved in tumorigenesis and related signaling pathways, with the aim of providing a reference for future exploration of ubiquitination.